Administrative Behaviors of School Administrators Correlated with the Operation of Student – Care Management System of Schools under The Secondary Educational Service Area Office 11 - Suwirat, Dachsri; Chareonsuk, Natcharee; Sungkhaosutthirak , Sathaporn (Journal of Roi Et Rajabhat University, 2021)
The objectives of this research were: 1) to study the administrative behaviors of school administrators under The Secondary Educational Service Area Office 11; 2) to study the operation of Student–Care Management System of schools under The Secondary Educational Service Area Office 11, and 3) to study the administrative behaviors of school administrators correlated with the operation of Student–Care Management System of schools under The Secondary Educational Service Area Office 11. The sample were 341 teachers, selected by simple random sampling using lottery method, of schools under The Secondary Educational Service Area Office 11. The research instrument was the 5-point Likert rating scale questionnaire. Data were analyzed by percentage, mean, standard deviation, and Pearson product moment correlation coefficient. The research results were as follows 1) The administrative behaviors of the school administrators was at a high level in overall and each aspect, ranked in descending order: leadership, personality, communication, motivation, and decision making, respectively 2) The operation of Student–Care Management System of the schools was at a high level in overall and each aspect, ranked in descending order: supervision and monitoring, evaluation, planning, and operation, respectively and 3) The administrative behaviors of the school administrators showed a strong correlation with the operation of Student–Care Management System of the schools (r = .71) at a significance level of .01.